PERSEPSI IKLAN, PERSEPSI HARGA DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA LOYALITAS PELANGGAN PRODUK LUWAK WHITE KOFFIE (Studi pada Mahasiswa FEB Universitas Stikubank (Unisbank) Semarang) - Sinta Maya Devi, 12.05.51.0044; Budi Setiawan, Mulyo (Students' Journal of Economic and Management, 2016)
This study aimed to analyze the influence of advertising, price perception, brand image to customer satisfaction and customer loyalty products Luwak White Koffie. The data used are primary data obtained directly from the original source in the form of a questionnaire. The sample in this study was the student of 2015-2016 at the Faculty of Economics and Business, University of Stikubank (UNISBANK) Semarang who consume Luwak White Koffie 86 people. The sampling technique is purposive sampling. The criteria for the samples used in this study are customers who already mengkosumsi products Luwak White Koffie at least twice or more. Test equipment used in this study testing the validity using factor analysis, reliability testing using Cronbach Alpha and hypothesis testing using multiple linear regression. The results of the analysis can be concluded that: Advertising has positive effect on customer satisfaction. Perception prices has positively affects customer satisfaction. Brand image has positively affects customer satisfaction. Advertising has positive effect on customer loyalty. Perception prices has positive effect on customer loyalty. Brand image has positively affects customer loyalty. Customer satisfaction has positive effect on customer loyalty. Customer satisfaction does not mediate the effect of advertising on customer loyalty. Customer satisfaction does not mediate the effect of price perception on customer loyalty. Customer satisfaction does not mediate the effect of brand image on customer loyalty. Keywords: advertising, perception of price, brand image, customer satisfaction and customer loyalty